2015
DOI: 10.1111/bjd.13598
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observational study of afamelanotide in 115 patients with erythropoietic protoporphyria

Abstract: SummaryBackground In erythropoietic protoporphyria (EPP), an inherited disease of porphyrin-biosynthesis, the accumulation of protoporphyrin in the skin causes severely painful phototoxic reactions. Symptom prevention was impossible until recently when afamelanotide became available. Afamelanotide-induced skin pigmentation has statistically significantly improved light-tolerance, although the clinical significance of the statistical effect was unknown. Objectives To assess clinical effectiveness by recording c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 36 publications
9
89
0
Order By: Relevance
“…One hotspot of current research is afamelanotide, which is a tridecapeptide that simulates human alpha melanocyte stimulating hormone (α-MSH), could bind to the melanocortin 1 receptor of melanocytes and promote the formation of epidermal melanin. Melanin can absorb, disperse, and reduce ultraviolet (UV), scavenging of free radicals, antioxidant, thereby reducing light-induced skin damage and alleviating photosensitive skin pain (Harms et al, 2009;Biolcati et al, 2015;Langendonk, 2015). Langendonk et al (2015) through a randomized, double-blind, multi-center, placebo control trial in the European Union and the United States found that afamelanotide, compared with the placebo, significantly increased the duration of sun exposure without photosensitive pain and improved the quality of life of EPP patients, and side effects are infrequent and acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…One hotspot of current research is afamelanotide, which is a tridecapeptide that simulates human alpha melanocyte stimulating hormone (α-MSH), could bind to the melanocortin 1 receptor of melanocytes and promote the formation of epidermal melanin. Melanin can absorb, disperse, and reduce ultraviolet (UV), scavenging of free radicals, antioxidant, thereby reducing light-induced skin damage and alleviating photosensitive skin pain (Harms et al, 2009;Biolcati et al, 2015;Langendonk, 2015). Langendonk et al (2015) through a randomized, double-blind, multi-center, placebo control trial in the European Union and the United States found that afamelanotide, compared with the placebo, significantly increased the duration of sun exposure without photosensitive pain and improved the quality of life of EPP patients, and side effects are infrequent and acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…Opaque topical sunscreens or UVB phototherapy may improve the tolerance of light. Symptom prevention was impossible until 2006 when afamelanotide (Scenesse ® ), a melanocyte-stimulating hormone analogue that induces epidermal melanin skin-tanning and has an anti-inflammatory effect on the skin [53,54], became available. From 2006 through 2015, the 16 mg afamelanotide implants have shown good clinical effectiveness, with a reduction in patients' sun sensitivity, an improvement in their quality of life quality and, in EPP, good safety with long-term use [54].…”
Section: Physiopathology and Treatmentmentioning
confidence: 99%
“…Pharmacological approaches have included pharmaceutical-grade b-carotene, narrow wave UVB phototherapy, cysteine, afamelanotide, antihistamines, and vitamin C (Table 1) (Sawyer et al, 1980;Krook and Haeger-Aronsen, 1982;Mathews-Roth et al, 1994;Collins and Ferguson, 1995;Warren and George, 1998;Wahlin et al, 2011a;Fabrikant et al, 2013;Tintle et al, 2014;Biolcati et al, 2015;Langendonk et al, 2015;Lengweiler et al, 2015;Minder and Schneider-Yin, 2015). Minder et al (2009) reviewed the treatment options for dermal photosensitivity in EPP in 2009 and concluded that the data were insufficient to prove efficacy of any treatments studied in EPP.…”
Section: Clinical Manifestations and Management Of Ppix Toxicitymentioning
confidence: 99%
“…Minder et al (2009) reviewed the treatment options for dermal photosensitivity in EPP in 2009 and concluded that the data were insufficient to prove efficacy of any treatments studied in EPP. Since then, controlled trials have demonstrated improved light tolerance in EPP and XLP with afamelanotide, an a-melanocytestimulating hormone analog that increases skin melanogenesis (Harms et al, 2009;Fabrikant et al, 2013;Biolcati et al, 2015;Langendonk et al, 2015).…”
Section: Clinical Manifestations and Management Of Ppix Toxicitymentioning
confidence: 99%
See 1 more Smart Citation